Mechanisms of Participation in Vocational Education and Training in Europe - Milmeister, Paul; Rastoder, Merlin; Houssemand, Claude (Frontiers in Psychology, 2022)
This article aims to analyze participation in vocational education and training in Europe. First, we study the differences between VET approaches in Europe. Secondly, a sociological analysis is provided. When VET systems were first created, aspects such as work culture or diverging political concerns led to different responses in the various countries. Thirdly, we present a psychological approach of the educational and vocational choice. This choice is made by comparing profession images with one’s own self-image. Finally, we propose a multidisciplinary explanatory model of the vocational choice, based on sociological and psychological dimensions. In conclusion, we propose several plans of action in order to achieve good student flow management with regard to educational choice, and improved valorization of the VET track.